2020
DOI: 10.3892/mmr.2020.10939
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of RIPK4 inhibits epithelial‑mesenchymal transition by inactivating the Wnt/β‑catenin signaling pathway in osteosarcoma

Abstract: receptor interacting protein kinase 4 (riPK4) is a serine/threonine kinase that plays an important role in the regulation of cell proliferation, invasion and metastasis in several malignancies; however, its clinical significance and biological function in osteosarcoma (oS) remains unknown. In the present study, the RIPK4 expression level was significantly upregulated in oS tissues and cell lines. High riPK4 expression was positively associated with larger sized tumors, advanced enneking stage and poor prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…RIPK4 has been implicated in the progression of numerous tumors [ 8 , 9 , 10 , 11 , 12 , 13 , 28 , 29 ]; however its role in melanoma remained unresolved. Our study fills this gap because it is the first to reveal the functional role of RIPK4 in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK4 has been implicated in the progression of numerous tumors [ 8 , 9 , 10 , 11 , 12 , 13 , 28 , 29 ]; however its role in melanoma remained unresolved. Our study fills this gap because it is the first to reveal the functional role of RIPK4 in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway is an important molecular signaling pathway with the ability to regulate biological processes such as apoptosis and differentiation [254][255][256][257]. A number of studies have shown that the Wnt signaling pathway contributes to increased invasion and malignancy of tumor cells via EMT induction [258][259][260]. The inhibition of Wnt by onco-suppressor factor Numb suppresses EMT in cancer cells, thereby illustrating the role of Wnt as an upstream mediator of EMT [261].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…As mentioned above, RIPK4 expression is positively associated with favorable prognosis in tongue SCC and lung adenocarcinoma (49,56). By contrast, increased RIPK4 expression predicts a poor prognosis in cervical SCC, pancreatic cancer, bladder cancer, and osteosarcoma (21,46,58,60). RIPK4 is a novel and independent prognostic factor, which may be used to identify patients at risk and guide individualized treatment.…”
Section: Discussionmentioning
confidence: 95%
“…RIPK4 knockdown in A2780 and COV434 ovarian cancer cells could inhibit β-catenin accumulation and RIPK4 overexpression could promote ovarian cancer in a xenograft tumor model ( 20 ). In addition, RIPK4 was significantly upregulated in osteosarcoma and RIPK4 knockdown suppressed EMT by inactivating Wnt/β-catenin signaling ( 60 ). RIPK4 promoted Wnt signaling, implying that RIPK4 overexpression might be involved in the development of certain tumor types.…”
Section: The Role Of Ripk4 In Carcinogenesismentioning
confidence: 99%